1993
DOI: 10.1210/endo.132.1.8380388
|View full text |Cite
|
Sign up to set email alerts
|

Presence and characterization of glucagon-like peptide-1(7-36) amide receptors in solubilized membranes of rat adipose tissue.

Abstract: Specific binding of [125I]glucagon-like peptide-1(7-36)amide ([125I]GLP-1(7-36)amide) to solubilized rat adipose tissue membranes was found to be dependent on temperature, time, and membrane protein concentration and readily dissociated. GLP-1(1-36)amide, GLP-2, or glucagon (10(-6) M) did not compete with [125I]GLP-1(7-36)amide binding. Half-maximal binding was achieved with 8 x 10(-10) M unlabeled GLP-1(7-36)amide, and the Scatchard plot revealed the presence of high and low affinity binding sites with Kd val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…These results are comparable with those obtained in membrane fractions from rat brain (Calvo et al . 1995) and rat adipose tissue (Valverde et al . 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable with those obtained in membrane fractions from rat brain (Calvo et al . 1995) and rat adipose tissue (Valverde et al . 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GLP-1 receptors have been found in the endocrine pancreas,24 adipose tissue,25and stomach 2627 Moreover, nerves containing GLP-1 have been identified in the brain 28…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Also, GLP-1 was shown to stimulate basal and/or insulin-induced glucose transport in rat adipocytes 8,17 and 3T3-L1 cells, 35 and to increase glycogen synthesis in rat fat pieces. 8 By [ 125 I]GLP-1 binding studies, speci®c GLP-1 receptors were found in solubilized membranes of rat 13 and human adipose tissue, 12 and by PCR and Southern blot analysis, using the pancreatic GLP-1 receptor cDNA probe, the presence of mRNA for this receptor in rat epididymal fat and 3T3-L1 adipocytes was detected. 11 The exact structure of the GLP-1 receptors in this tissue, and in liver, remain to be elucidated, however.…”
Section: Discussionmentioning
confidence: 99%